Analisis Sentimen dan Respon Publik terhadap Creative Entertainment - Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom, Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
This research highlights the importance of sentiment analysis and public response in the entertainment industry. Through social media data, patterns of response to creative content such as movies, TV shows, and games can be identified. Factors such as production quality, narrative,and cultural context influence public sentiment. The integration of this analysis in marketing strategies allows for the creation of more relevant and responsive content. Case studies, such as Electronic Arts' use of sentiment analysis, emphasize the importance of this approach in strategic  decision-making in the entertainment industry. This research method involves analyzing social media data to understand public response to creative entertainment content, the results of this study reveal patterns of public response to creative entertainment content such as movies, television shows, and video games through social media data analysis. Factors influencing positive and negative sentiment have been identified, including production quality, narrative, characters, themes, and social and cultural context. The integration of sentiment analysis resultsinto marketing strategies and content development in the entertainment industry can improve content quality and responsiveness to audience needs. By better understanding public response, entertainment industry practitioners can create content that is more relevant and engaging to their audiences.